Investigating “Man’s Relation to Reality”: Peter Winch, the Vanishing Shed and Metaphysics after Wittgenstein - Lagerspetz, Olli (Wiley, 2022)
Peter Winch believed that the central task of philosophy was to investigate ‘the force of the concept of reality’ in human practices. This involved creative dialogue with critical metaphysics. In ‘Ceasing to Exist’, Winch considered what it means to judge that something unheard-of has happened. Referring to Wittgenstein, Winch argued that judgments concerning reality must relate our observations to a shared ‘flow of life’. This implies criticism of the form of epistemology associated with metaphysical realism. Just as, according to Wittgenstein, a sentence has no fixed meaning in isolation, an observation does not constitute knowledge outside shared human practices.